"An unusual presentation of colonic mucormycosis mimicking carcinoma colon- a surgeon's perspective". (2015) - Kumar Debata, Prasanna; Keshari Panda, Sangram; Dash, Atmaranjan; Mohanty, Ramakant; Narayan Mallick, Biranchi; Tadu, Debabrata; g nath, Vivek; Sahoo, Abhinash
Highlights: Mucormycosis is a rare but invasive opportunistic fungal infection. We report an unusual presentation of mucormycosis of ascending colon that was simulating carcinoma colon. Knowing this unusual presentation, surgeon need to maintain a high index of suspicion and perform timely & appropriate diagnostic evaluation to improve patient outcome. Abstract: Introduction: Mucormycosis caused by order mucorales, an ubiquitous saprophytic mold found in soil and organic matter worldwide, is a rare but invasive opportunistic fungal infection. Gastrointestinal mucormycosis is the most uncommon clinical presentation being particularly rare, accounted for 4–7% of all cases. Presentation of case: We report an unusual presentation of mucormycosis of ascending colon that was simulating carcinoma colon. Discussion: GI mucormycosis most commonly involves the stomach (57.5%), followed by the colon (32.3%) and the ileum (6.9%). Initial presentations may be abdominal pain and distension, fever, and diarrhoea. Colonic mucormycosis presenting as a mass with altered bowel habit, melena and abdominal pain in our case is extremely difficult to differentiate it from carcinoma colon. A definitive diagnosis of mucormycosis is almost always ascertained by histopathological evidence of fungal invasion of tissue. Conclusion: Knowing these unusual presentations of this disease, surgeon need to maintain a high index of suspicion and perform timely and appropriate diagnostic evaluation to improve patient outcome. Prompt diagnosis, reversal of predisposing conditions, and aggressive surgical debridement remain cornerstones of therapy for this deadly disease.